Insect in vitro System for Toxicology Studies — Current and Future Perspectives - Cc, Sheeja; Arun, Damodaran; Divya, Lekha (Frontiers in Toxicology, 2021)
In vitro cell culture practices are valuable techniques to understand the mechanisms behind vital in vivo biological processes. In vitro cells have helped us to attain a deeper understanding of functions and mechanisms conserved in the course of evolution. Toxicology studies are inevitable in drug discovery, pesticide development, and many other fields that directly interact with human beings. The proper involvement and regulatory steps that have been taken by animal ethical societies in different parts of the world resulted in the reduced in vivo use of mammals in toxicological studies. Nevertheless, experimental animals are being killed where no replacement is available. The use of mammals could be reduced by using the in vitro systems. Nowadays, invertebrate cell lines are also play important role in toxicology testing. This review analyzes the cause and consequence of insect in vitro models in toxicology studies.